Pengaruh Likuiditas dan Profitabilitas Terhadap Agresivitas Pajak (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2019 - 2021) - Syafira Ramadhea Jr; Dita Maretha Rissi; Lisa Amelia Herman (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
This study aims to obtain empirical evidence on (1) the effect of liquidity on tax aggressiveness and (2) the effect of profitability on tax aggressiveness. The object of this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) for the period 2019 – 2021. This type of research is quantitative. The population of this study was 189 manufacturing companies listed on the Indonesia Stock Exchange for the period 2019-2021. The research sample consisted of 24 manufacturing companies. Sampling technique is to use purposive sampling technique. The Data used in the form of secondary data from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange. Hypothesis testing of this study using multiple linear analysis method with liquidity and profitability as independent variables, and tax aggressiveness as the dependent variable. Data processing with the help of SPSS application version 24 for windows. The results showed that liquidity has no significant negative influence on tax aggressiveness, but profitability has a significant positive influence on tax aggressiveness.